Structural design and mechanical behavior of alligator (Alligator mississippiensis) osteoderms - Sun, Chang-Yu; Chen, Po-Yu (Acta biomaterialia, 2013)
Alligator is a well-adapted living fossil covered with dorsal armor. This dermal shield consists of bony plates, called osteoderms, interconnected by sutures and non-mineralized collagen fibers, providing a dual function of protection and flexibility. Osteoderm features a sandwich structure, combining an inner porous core and an outer dense cortex, to offer enhancements for stiffness and energy absorbance. In this study, we investigated the multi-scale structure and mechanical behaviors of the American alligator (Alligator mississippiensis) osteoderm. Microcomputed tomography was applied to reveal the complex neurovascular network. Through the observation under optical and scanning electron microscopes, the osteoderm was found to consist of woven bone in the dorsal region and lamellar-zonal bone in the ventral region. Nanoindentation and compressive tests were performed to evaluate the mechanical properties of osteoderms. The varying mineral contents and porosity result in a graded mechanical property: a hard and stiff dorsal cortex gradually transform to a more compliant ventral base. Three protective mechanisms optimized for alligator osteoderms were proposed and elucidated.